160 Involving men in cervical cancer prevention: a qualitative enquiry into male perspectives on screening and HPV vaccination in mid-western uganda. (18th September 2019) - de Fouw, M; Stroeken, Y; Musheshe, M; Reis, R; Beltman, J
Abstract : Objectives: Evidence-based preventive strategies for cervical cancer in low-resource setting have been developed, but implementation is challenged and uptake remains low. Women and girls experience barriers to attend screening and human papilloma virus (HPV) vaccination programs. Male support has been proven successful in uptake of other reproductive healthcare services. This qualitative study aimed to understand the perspectives of males on cervical cancer screening and HPV vaccination in Uganda. Methods: Focus group discussions were conducted with men aged 25 to 60 years, who were married and/or had daughters, in Kagadi district, Mid-Western Uganda. All interviews were transcribed verbatim and thematically analyzed using an inductive approach. Results: Men were willing to support their wives for screening and their daughters for HPV-vaccination. Misperceptions, such as family planning and poor personal hygiene thought to cause cervical cancer, and misperception of the preventative aspect of screening and vaccination were common. Women with cervical cancer suffer from stigmatization and family problems due to loss of fertility, less marital sexual activity, domestic violence and decreased economic productivity. Conclusions: Ugandan men were willing to support cervical cancer prevention for their wives and daughters. Limited knowledge among men about the causes of cervical cancer, the preventative aspect and target groups for HPV-vaccination and screening can limit uptake of both services. Screening and vaccination programs should actively involve men in awareness to increase uptake and acceptance of the programs.